Analysis of LQ45 Stock Trading Volume and Stock Return in 2019 Pre and Post Election - Tubagus Fauzan; Lely Fera Triani; Ali Muktiyanto (PT FORMOSA CENDEKIA GLOBAL, 2025)
The global era can quickly grow the economy stretch in a country, one of which is the investment climate that is currently growing, especially in Indonesia. Capital markets have an important role in economic life, especially in the process of allocating public funds. Political events become a source of information absorbed by capital market actors, then used by actors as a basis for obtaining future profits. The objectives of this study were to analyze the conditions of Trading Volume Activity, and Abnormal Return on LQ 45 Companies in Before and After the 2019 ELECTION Event. The variables used in this study consisted of 2 variables namely Trading Volume Activity, and Abnormal Return. The test tool used in this study is the analysis of 2 dependent variables with the Wilcoxon Signed Rank Test using the Statistical analysis package Package for the Social Sciences version 21.0. Data comes from 45 companies registered in LQ 45, the period 5 days before and 5 after the 2019 ELECTION event. The results showed that there were differences in Trading Volume Activity in LQ45 companies, and there was no Abnormal Return difference between the two testing times.